Oil Prices, Control of Corruption, Governance, and Economic Growth Nexus in Saudi Arabia - Mahmood, Haider (International Journal of Energy Economics and Policy, 2021)
This study examines the impact of control of corruption and the effectiveness of governance on the economic growth in Saudi Arabia using the latest cointegration approach of Pesaran et al. (2001) and Kripfganz and Schneider (2019). We utilize unit root and cointegration tests using a maximum available sample from 1996-2019. The effect of control of corruption is found insignificant on economic growth, and a positive effect of governance is found in the long-run. The study is corroborated that good governance is an appropriate tool for economic growth in the long-run. Moreover, oil prices show a positive effect on economic growth both in the long and short run. It corroborates that the economic growth of Saudi Arabia is oil price dependent. The short-run effects of governance and control of corruption are found insignificant. Hence, a long period with good governance is required to support the economic growth of the Kingdom. So, it is recommended that the quality of governance should be enhanced to support economic growth. Keywords: Control of corruption, governance, economic growth, oil prices JEL Classifications: P16, O43, O13 DOI: https://doi.org/10.32479/ijeep.11181